Emotion recognition through static faces and moving bodies: a comparison between typically developed adults and individuals with high level of autistic traits - Actis-Grosso, Rossana; Bossi, Francesco; Ricciardelli, Paola (Frontiers in Psychology, 2015)
We investigated whether the type of stimulus (pictures of static faces vs. body motion) contributes differently to the recognition of emotions. The performance (accuracy and response times) of 25 Low Autistic Traits (LAT group) young adults (21 males) and 20 young adults (16 males) with either High Autistic Traits (HAT group) or with High Functioning Autism Spectrum Disorder was compared in the recognition of four emotions (Happiness, Anger, Fear and Sadness) either shown in static faces or conveyed by moving bodies (patch-light displays, PLDs). Overall, HAT individuals were as accurate as LAT ones in perceiving emotions both with faces and with PLDs. Moreover, they correctly described non-emotional actions depicted by PLDs, indicating that they perceived the motion conveyed by the PLDs per se. For LAT participants, happiness proved to be the easiest emotion to be recognized: in line with previous studies we found a happy face advantage for faces, which for the first time was also found for bodies (happy body advantage). Furthermore, LAT participants recognized sadness better by static faces and fear by PLDs. This advantage for motion kinematics in the recognition of fear was not present in HAT participants, suggesting that i) emotion recognition is not generally impaired in HAT individuals, ii) the cues exploited for emotion recognition by LAT and HAT groups are not always the same. These findings are discussed against the background of emotional processing in typically and atypically developed individuals.